Hubungan Tingkat Pengetahuan Terhadap Kepatuhan Pengobatan Pada Pasien Tuberkulosis Di Puskesmas Pringsewu - Yuniyarti, Lisa; Pratiwi, Mida; Syamsuri, Eddy; Putri, Diah Kartika (Peneliti.net, 2025)
Mycobacteria tuberculosis is the infectious agent that causes tuberculosis (TB). With a CDR of 41.49%, Lampung Province is among those with the lowest rates of TB case detection. Pringsewu Health Center has more patients receiving TB treatment than any other facility, according to SITB. The research objective was to determine the knowledge level and compliance as well as the correlation between the knowledge level and compliance with tuberculosis treatment at the Pringsewu Public Health Center. This research type is quantitative analytical research with a cross-sectional approach. The sample in this study was all tuberculosis patients who were undergoing treatment at the Pringsewu Public Health Center, totaling 33 people. The results showed that 26 (78.8%) respondents had good knowledge and 7 (21.2%) respondents had sufficient knowledge. Patients with high compliance were 21 (63.6%) respondents, moderate compliance was 11 (33.3%) respondents and low compliance was 1 (3.0%) respondent. The chi-square analysis of the correlation between knowledge and treatment compliance showed that there was a correlation between knowledge and treatment compliance with a p-value = 0.000 (p> 0.05). The research conclusions showed that the majority of respondents' knowledge was good (78.8%), the majority of respondents' compliance was high (63.6%) and there was a correlation between knowledge and treatment compliance in tuberculosis patients at the Pringsewu Public Health Center